2014
DOI: 10.1021/ol501306u
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-Functionalized Locked Nucleic Acids: Oligonucleotides with Extraordinary Binding Affinity, Target Specificity, and Enzymatic Stability

Abstract: Three different C5-carbohydrate-functionalized LNA uridine phosphoramidites were synthesized and incorporated into oligodeoxyribonucleotides. C5-Carbohydrate-functionalized LNA display higher affinity toward complementary DNA/RNA targets (ΔTm/modification up to +11.0 °C), more efficient discrimination of mismatched targets, and superior resistance against 3'-exonucleases compared to conventional LNA. These properties render C5-carbohydrate-functionalized LNAs as promising modifications in antisense technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
4
11
0
Order By: Relevance
“…Hrdlicka et al reported that the C5functionalization of LNA-U substantially improves resistance against 3′-exonuclease hydrolysis, probably due to the steric effects of the substituents. 36,38,[39][40][41] However, which phosphate scission (5′-or 3′-) is influenced by the C5-modification is unknown. Therefore, we examined the enzyme stability of two types of ONs modified with LNA-U Az : ONs 10 and 11 were used to evaluate 3′-phosphate scission and ONs 12 and 13 were used to evaluate 5′-phosphate scission.…”
Section: Nuclease Resistance Of Ons Modified With Lna-u Azmentioning
confidence: 99%
See 1 more Smart Citation
“…Hrdlicka et al reported that the C5functionalization of LNA-U substantially improves resistance against 3′-exonuclease hydrolysis, probably due to the steric effects of the substituents. 36,38,[39][40][41] However, which phosphate scission (5′-or 3′-) is influenced by the C5-modification is unknown. Therefore, we examined the enzyme stability of two types of ONs modified with LNA-U Az : ONs 10 and 11 were used to evaluate 3′-phosphate scission and ONs 12 and 13 were used to evaluate 5′-phosphate scission.…”
Section: Nuclease Resistance Of Ons Modified With Lna-u Azmentioning
confidence: 99%
“…Recently, Hrdlicka et al combined sugar-and nucleobase-modifications and developed C5-functionalized LNA uridine (U) derivatives with various functional groups via an alkyne linker. [36][37][38][39][40][41] They revealed that C5-functionalized LNA-U exhibited prominent affinity at elevated temperatures toward RNA targets, extraordinary discrimination of singly mismatched RNA strands, and improved resistance against degradation by 3′-exonucleases. Moreover, they used C5-fluorophore-functionalized LNA-U to discriminate single nucleotide polymorphisms (SNPs).…”
Section: Introductionmentioning
confidence: 99%
“…They can be installed terminally during ON synthesis either at the 5′-end via phosphoramidite chemistry, or used together with a solid support in the 3′-end as has been realized for the previous described triantennary carbohydrate linkers. The groups of Hrdlicka and Kobayashi have modified LNA-U and 2′-deoxyuridine, respectively, in the C5 position of the pyrimidine base with an acetylene linked monosaccharide under Sonogashira conditions. , As in base J, formation of a direct glycosidic bond between a carbohydrate and a hydroxyl modified base of the nucleoside is also possible. , The group of Lönnberg exchanged the whole nucleobase by a triantennary carbohydrate linker using oxime and azide–alkyne cycloaddition chemistry . Beigelman and co-workers introduced several galactosamines in the 2′-position of deoxyribose through an amide linker strategy .…”
Section: Introductionmentioning
confidence: 99%
“…Modified nucleotide monomers are widely used within ON drug development to enhance the affinity and selectivity toward complementary nucleic acids and to improve the nuclease resistance. Locked nucleic acid (LNA) monomers in which the ribofuranose moiety is locked in a C-3′- endo (North type) conformation by the introduction of an oxomethylene linker between the C2′ and C4′ atoms of the ribose ring is a prominent example inducing a very significant increase in duplex and triplex stabilities. Several structurally modified LNA analogues have been synthesized in the past few years to enhance binding specificity, stability and biodistribution. Most of these modifications have involved the linker between the C2′ and C4′ atoms as exemplified by 2′-amino-LNA, carba-LNA, spirocyclopropylene-LNA and methylene-carba-LNA but also modifications/attachments in the C5 position of the pyrimidine base. ,, One recent example of the latter involved carbohydrate modified LNA derivatives from the Hrdlicka laboratory . They compared glucose, galactose and lactose modified LNA nucleotides incorporated into ONs in view of binding activity, specificity and nuclease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Bioorthogonal chemistry, featuring phosphorylation, esterification, amidation, alkynylation, cycloaddition, and cross‐coupling reactions, among others, have been used for the combination of modified nucleic acids with small‐molecule drugs, delivery vectors, and/or imaging probes. In these combination approaches, the nucleic acid bioconjugates are designed to target multiple biological markers in tumors leading to synergistic antitumor responses.…”
Section: Introductionmentioning
confidence: 99%